Approach to androgen excess in women: Clinical and biochemical insights. (29th March 2022) - Cussen, Leanne; McDonnell, Tara; Bennett, Gillian; Thompson, Christopher J.; Sherlock, Mark; O'Reilly, Michael W.
Abstract: Androgen excess in women typically presents clinically with hirsutism, acne or androgenic alopecia. In the vast majority of cases, the underlying aetiology is polycystic ovary syndrome (PCOS), a common chronic condition that affects up to 10% of all women. Identification of women with non‐PCOS pathology within large cohorts of patients presenting with androgen excess represents a diagnostic challenge for the endocrinologist, and rare pathology including nonclassic congenital adrenal hyperplasia, severe insulin resistance syndromes, Cushing's disease or androgen‐secreting tumours of the ovary or adrenal gland may be missed in the absence of a pragmatic screening approach. Detailed clinical history, physical examination and biochemical phenotyping are critical in risk‐stratifying women who are at the highest risk of non‐PCOS disorders. Red flag features such as rapid onset symptoms, overt virilization, postmenopausal onset or severe biochemical disturbances should prompt investigations for underlying neoplastic pathology, including dynamic testing and imaging where appropriate. This review will outline a proposed diagnostic approach to androgen excess in women, including an introduction to androgen metabolism and provision of a suggested algorithmic strategy to identify non‐PCOS pathology according to clinical and biochemical phenotype.